2019
DOI: 10.21037/jtd.2019.07.35
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic surgery for ectopic mediastinal parathyroid tumor: subxiphoid and lateral thoracic approach

Abstract: Background: This study aimed to investigate the initial results of an endoscopic surgical approach for the treatment of intramediastinal ectopic parathyroid adenoma and to evaluate the effectiveness of a singleincision resection using the subxiphoid approach. Methods: Five cases of patients (1.89%) were diagnosed with ectopic mediastinal parathyroid tumor and underwent resection from 2008 to 2017 in Fujita Health University Hospital. They were retrospectively analyzed. Results: Four patients underwent single-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For masses located deeper inside the mediastinum, instead of standard open techniques such as thoracotomy, median sternotomy and manubriotomy, minimally invasive approaches are developed as well (video-assisted mediastinal surgery-VAMS [13,17] and VATS [20][21][22][23]. It is considered "first line" treatment option for patients with mediastinal parathyroid adenoma located deeper than the brachiocephalic vein [20].…”
Section: Discussionmentioning
confidence: 99%
“…For masses located deeper inside the mediastinum, instead of standard open techniques such as thoracotomy, median sternotomy and manubriotomy, minimally invasive approaches are developed as well (video-assisted mediastinal surgery-VAMS [13,17] and VATS [20][21][22][23]. It is considered "first line" treatment option for patients with mediastinal parathyroid adenoma located deeper than the brachiocephalic vein [20].…”
Section: Discussionmentioning
confidence: 99%
“…The latest studies showed that single-incision mediastinal tumour resection by subxiphoid access is a useful endoscopic surgical approach for the treatment of mediastinal ectopic parathyroid adenomas. The post-thoracotomy pain syndrome is limited, and the aesthetic outcomes are protreptic [51]. Most patients undergoing VATS do not suffer from serious complications, but some may require conversion to median sternotomy for thymoma removal in cases of false positive pre-operative imaging.…”
Section: Surgical Approach To Ectopic Mediastinal Parathyroid Adenomamentioning
confidence: 99%
“…Ectopic mediastinal PAs (MEPA), which account for ~1–2% of all PAs, are recognized as major cause for persistent PHPT with severe clinical manifestations [ 5 ]. With surgical MEPA-resection as the only therapeutic option, key points for successful surgical treatment are: (i) an adequate preoperative imaging modality to accurately localize the ectopic PA and (ii) the radical resection of all possible ectopic PA-including mediastinal tissue [ 6 , 7 ]. With modern imaging techniques as essential prerequisite, the uniportal subxiphoid approach is an excellent surgical technique for a complete ectopic mediastinal parathyroidectomy.…”
Section: Introductionmentioning
confidence: 99%